Distribution of illness of orthopaedic outpatient department in a tertiary care teaching hospital in West Bengal: a cross sectional study - Kum, Ajayar; Dalai, Chanchal Kumar; Banerjee, Santanu (International Journal of Research in Medical Sciences, 2017)
Background: Orthopaedic Outpatient Department (OPD) is an important part of health care system. Patients coming with different illness for treatment. Distribution pattern of illness represents the area from where patients come for treatment. Methods: Cross sectional, Observation Study. The patients who had willingly participated were enrolled on the basis of subject selection criteria. Prescriptions were collected from newly patients attending the Orthopaedics OPD. No follow up visit was done. Results: Male patients attended more than female gender (62% vs 38%). 18-30 years age group attended OPD much than another group (32.5%). Trauma is an important contributing factor (38.5%). History of trauma was seen more in male gender group and among 18-30 years age group. Low back pain is common problem. (29.5%). Conclusions: Low back pain is the common problem among patients attended Orthopaedic OPD. Trauma is an important contributing factor among 18-30 years age group.